Ultra-Formulas for Conjugate Gradient Impulse Noise Reduction from Images - Hassan , Basim A.; Taha, Mohammed W. (Iraqi Journal of Science, 2026)
In this research, a new coefficient of conjugate gradient technique is identified which is used for solving issues related to image restoration. This coefficient is derived using Perry's conjugacy condition and the quadratic model. The algorithms have been shown to exhibit global convergence and possess the descent property. Through numerical testing, the new method demonstrated a significant improvement. It has been shown that the innovative conjugate gradient method works better than the conventional FR conjugate gradient technique.